2016
DOI: 10.1021/acs.jpclett.6b01922
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Trend in Stability of Xe–F Compounds under Pressure Driven by Xe–Xe Covalent Bonds

Abstract: Xenon difluoride is the first and the most stable of hundreds of noble-gas (Ng) compounds. These compounds reveal the rich chemistry of Ng's. No stable compound that contains a Ng-Ng bond has been reported previously. Recent experiments have shown intriguing behaviors of this exemplar compound under high pressure, including increased coordination numbers and an insulator-to-metal transition. None of the behaviors can be explained by electronic-structure calculations with fixed stoichiometry. We therefore condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 47 publications
4
79
1
Order By: Relevance
“…For Kr 2 F, our structure investigations identified a phase with I4/mcm symmetry, one that remains the lowest-enthalpy structure in the whole pressure range studied. This polymorph is isostructural with a previously proposed high-pressure phase of Xe 2 F [44]. Similarly to that structure, it contains an interpenetrating network of graphitic Kr layers (Figure 4a) with a Kr-Kr bond of about 2.5 Å at 150 GPa, which is ca 8% shorter than the Kr-Kr separation in solid krypton at the same pressure ( Table 1).…”
Section: The 50-200 Gpa Pressure Rangesupporting
confidence: 65%
See 4 more Smart Citations
“…For Kr 2 F, our structure investigations identified a phase with I4/mcm symmetry, one that remains the lowest-enthalpy structure in the whole pressure range studied. This polymorph is isostructural with a previously proposed high-pressure phase of Xe 2 F [44]. Similarly to that structure, it contains an interpenetrating network of graphitic Kr layers (Figure 4a) with a Kr-Kr bond of about 2.5 Å at 150 GPa, which is ca 8% shorter than the Kr-Kr separation in solid krypton at the same pressure ( Table 1).…”
Section: The 50-200 Gpa Pressure Rangesupporting
confidence: 65%
“…In case of Xe2F, Peng et al indicated formation of covalent Xe-Xe bonds [44]. For Kr2F we find, however, that ELF values between nearest-neighbor Kr atoms do not exceed 0.15 (Figure 4c), which hints at lack of Kr-Kr covalent bonding within the graphitic layers.…”
Section: The 50-200 Gpa Pressure Rangementioning
confidence: 52%
See 3 more Smart Citations